Knowledge Construction from Border School in Multicultural Society - รุจิเสถียรทรัพย์ ธันยา; เจือไทย จิตติมา; ปัดไธสง สุรวุฒิ; สันคติประภา กิตติกร; จันทาภากุล นงลักษณ์ (Journal of Social Work and Social Administration, 2019)
This article aimed at analyzing educational experiences of the Border Patrol Police School students starting from the period before entering the school, their life during school education and after their graduation. The narrative approach was used to analyze the knowledge the Border Patrol Police School students gained from their educational experience under the educational system which was appropriately managed based on their conditions. The importance was paid to the analysis of conditions and factors leading to the educational inaccessibility among children and the youth in rural areas. In addition, the learning process and educational success of the Border Patrol Police School were investigated. The findings revealed that the equality and justice in education under the multicultural society could not be achieved by the standardized learning targets and principles. Thus, it is suggested that the alternative education should be provided for children and young people in the rural areas so that they can access a variety of knowledge and follow their own desirable lifestyle with dignity and equality.